Clinical investigation of intestinal fatty acid-binding protein (I-FABP) as a biomarker of SARS-CoV-2 infection. (December 2021) - Saia, Rafael Simone; Giusti, Humberto; Luis-Silva, Fábio; Pedroso, Karina de Jesus Bonicenha; Auxiliadora-Martins, Maria; Morejón, Karen Mirna Loro; Degiovani, Augusto Marcussi; Cadelca, Márcia Regina; Basile-Filho, Anibal
ABSTRACT: Objectives: SARS-CoV-2 exhibits tropism for the gastrointestinal tract; however, lesions in enterocytes and their correlation with disease severity and patient prognosis are still unknown. Methods: SARS-CoV-2 patients were enrolled in 5 medical centres in São Paulo, Brazil and their clinical characteristics and laboratory findings recorded. At admission, day 7 and day 14 of hospitalisation, plasma and urine samples were collected, and cytokine levels and intestinal fatty acid-binding protein (I-FABP) concentrations measured. Results: COVID-19 patients displayed ≈48-, 74- and 125-fold increased urinary I-FABP levels at admission ( n= 283; P <0.001), day 7 ( n =142; P <0.01) and day 14 ( n =75; P <0.01) of hospitalisation. Critically ill patients and nonsurvivors showed higher I-FABP concentrations compared with patients with less severe illness. At admission, infected patients demonstrated enhanced production of plasma interferon (IFN)-γ and interleukin (IL)-6. The receiver operating characteristic curve suggested I-FABP as a biomarker for COVID-19 disease severity at admission ( P <0.0001; Youden index=6.89; area under the curve=0.699). Patients with I-FABP ≥6.89 showed higher IL-6 and C-reactive protein levels ( P <0.001) at admission and had a prolonged length of hospital stay. Conclusions: Our findings revealed damage to enterocytes in SARS-CoV-2 infection, which is associated with illness severity, poor prognosis and exacerbated inflammatory response.